The Sleep-Like Nature of Early Mammalian Behavioral Rhythms: Theoretical Comment on Todd et al. (2010) - Corner, Michael A. (Behavioral Neuroscience, 2010)
Early sleep patterns lack several of the major defining physiological criteria used to identify sleep states in adult animals, but many typical aspects of mature sleep can nevertheless be demonstrated at surprisingly early stages of development. In Todd, Gibson. Shaw, & Blumberg (2010), the ability to compensate for enforced sleep deprivation is found to be present already shortly after birth in laboratory rats, an altricial mammalian species. Whereas the brainstem is capable of resisting enforced wakefulness by an increasing “pressure” to fall asleep, “catch-up” replacement of the lost sleep by means of longer subsequent sleep durations requires forebrain participation. This investigation represents an initial foray into the theoretically important area of the ontogeny of homeostatic regulatory mechanisms for behaviorally crucial neurophysiological processes. Reprinted by permission of the publisher.